Design and Synthesis of Novel Triazole-Isofroxadin Molecules: Docking Studies Against Inflammatory and Tuberculosis Targets (Indian Journal of Chemistry (IJC), 2025)
1,2,3-Triazole scaffolds are playing a vital role in various fields. These are not natural products but produced by synthetic chemists. Isafroxadin natural product and its 1,2,3-triazole derivatives were synthesized using Click protocol. Thus, generated new scaffolds were subjected to docking studies against Inflammatory and Tuberculosis activity.